Existence of isoperimetric regions in with density - Morgan, Frank; Pratelli, Aldo (Annals of Global Analysis and Geometry, 2013)
We prove the existence of isoperimetric regions in with density under various hypotheses on the growth of the density. Along the way, we prove results on the boundedness of isoperimetric regions.
Keywords: Isoperimetric sets; R-n with density; Existence of optimal sets; Boundedness of optimal sets